Whole body vibration in sport: a critical review - Costantino, C.; Gimigliano, R.; Olvirri, S.; Gimigliano, F. (The Journal of Sports Medicine and Physical Fitness, 2014)
Whole body vibration training is a recent area of study in athletic conditioning, health and rehabilitation. This paper provides a review of the effectiveness of this type of training in sport. A search was conducted across several electronic databases and studies on effects of whole body vibration training on sport performance were reviewed. Thirteen articles were included in the final analysis. The following variables were considered: participants investigated (sex and age), characteristics of the vibration (frequency and amplitude), training (type of sport, exposure time and intensity, tests used, type of study, effects examined and results obtained). This review considers proposed neural mechanisms and identifies studies that have demonstrated the effectiveness of WBV in sports. It considers where WBV might act and suggests that vibration can be an effective training stimulus. Future studies should focus on evaluating the long-term effects of vibration training and identify optimum frequency and amplitude, improve strength and muscular performance.